Systemic amyloidosis following inflammatory bowel disease, follicular lymphoma, and diffuse large B-cell lymphoma: a case report - Sukrisman, Lugyanti; Makmun, Dadang; Krisnuhoni, Ening (Medical Journal of Indonesia, 2024)
Systemic amyloidosis is a rare disorder characterized by the widespread deposition of misfolded amyloid proteins in several organs, leading to organ failure and potentially death if not promptly recognized. The occurrence of inflammatory bowel disease (IBD), follicular lymphoma, and diffuse large B-cell lymphoma (DLBCL) developing into systemic amyloidosis is uncommon. Here is a case of a 55-year-old Asian woman with a history of IBD, follicular lymphoma, and abdominal DLBCL who developed systemic amyloidosis affecting her gastrointestinal, cardiac, and renal organs. Gastrointestinal symptoms (abdominal pain and melena) initially manifested in this patient with systemic amyloidosis. She underwent treatment with three cycles of rituximab and bendamustine. However, she passed away after 2 months of hospitalization due to multiple organ failure. Hence, physicians must be vigilant in recognizing amyloidosis as a potential complication of lymphoma or other inflammatory diseases, as early recognition can contribute to improved clinical outcomes.